KHIYAR SEBAGAI UPAYA MEWUJUDKAN KEADILAN DALAM BISNIS ISLAMI - Hafizah, Yulia (At-Taradhi, 2012)
This article relooks at khiyar (the right to choose between continuing or aborting atransaction) that starts to be ignored in the current business world. It covers various forms ofkhiyar and the philosophy behind the concept. The importance of this right lies on the rule that atransaction has to accord with the principle of âan tarÃ¢dhin (both parties are happy with a giventransaction). Khiyar is embedded in every transaction: it automatically applies. But our contempo-rary and more complex trade world moves towards the abandonment of this right to choose. Anindication of this is the often found store policy that reads âan item that has been bought cannotbe returnedâ. This is why a serious thinking is needed to keep the khiyar exist, so justice in anytransaction can be preserved.